2020
DOI: 10.1111/bjhp.12398
|View full text |Cite
|
Sign up to set email alerts
|

Cancer and changes in facial appearance: A meta‐ethnography of qualitative studies

Abstract: Introduction. Living with an altered facial appearance as a result of treatment for cancer requires considerable psychological adjustment. As such it is essential that health care professionals understand the lived experience of people affected. This systematic review provides a meta-ethnography of studies that have explored the experience of changed facial appearance as a result of cancer. Methods.A search of four databases (Web of Science, CINAHL, PsycInfo, and Scopus) took place using terms relating to qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Significant nasal deformities can greatly affect first impressions and social interactions 19,20 . Research has demonstrated the influence of nasal appearance on selfidentity and mental health, underlining the critical need to ensure acceptable cosmetic outcomes 19,[20][21][22] . Radiation and surgery currently represent the two primary treatment options for NV carcinomas 8,9,11,13,[23][24][25] .…”
Section: Statement 5 Brachytherapy As Standard Of Carementioning
confidence: 99%
“…Significant nasal deformities can greatly affect first impressions and social interactions 19,20 . Research has demonstrated the influence of nasal appearance on selfidentity and mental health, underlining the critical need to ensure acceptable cosmetic outcomes 19,[20][21][22] . Radiation and surgery currently represent the two primary treatment options for NV carcinomas 8,9,11,13,[23][24][25] .…”
Section: Statement 5 Brachytherapy As Standard Of Carementioning
confidence: 99%
“…Link and colleagues (Link et al, 1989; see also Link & Phelan, 2013) identified three main coping orientations to face public stigma: secrecy, withdrawal, and education. Although FD is undoubtedly visible, many people with FD engage in measures to conceal their FD (e.g., cosmetic cream, prosthesis, surgery), often to ease outings in public places (Keys et al, 2021;Thompson et al, 2020) and in social interactions (Bemmels et al, 2013;Myhre et al, 2021). Their stigma is thus partially concealed, because it may not be readily apparent to others.…”
Section: Coping With the Social Stigma Of Facial Differencementioning
confidence: 99%
“…In addition to concealment, people with FD may also adopt avoidant behaviors and social withdrawal, in order to prevent stigma. However, this reduces opportunities to socialize and access social support (Griffiths et al, 2012;Halioua et al, 2017;Lanigan & Cotterill, 1989;Magin et al, 2008;Thompson et al, 2020).…”
Section: Coping With the Social Stigma Of Facial Differencementioning
confidence: 99%
“…In addition to the aggravating factor of skin cancer, these data also include the 6th position in the world ranking occupied by head and neck cancer, a modality also strongly associated with facial mutilations, resulting from the low socioeconomic conditions of the patients. These anomalies can be embarrassing for the bearer and often make these individuals traumatized, embarrassed and psychologically debilitated [2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%